Application of third-generation sequencing technology in the genetic testing of thalassemia - Weihao Li; Yanchou Ye (Molecular Cytogenetics)
Abstract Thalassemia is an autosomal recessive genetic disorder and a common form of Hemoglobinopathy. It is classified into α-thalassemia and β-thalassemia. This disease is mainly prevalent in tropical and subtropical regions, including southern China. Severe α-thalassemia and intermediate α-thalassemia are among the most common birth defects in southern China. Intermediate α-thalassemia, also known as Hb H disease, is characterized by moderate anemia. Severe α-thalassemia, also known as Hb Bart’s Hydrops fetalis syndrome, is a fatal condition. Infants with severe β-thalassemia do not show symptoms at birth but develop severe anemia later, requiring expensive treatment. Most untreated patients with severe β-thalassemia die in early childhood. Screening for thalassemia carriers and genetic diagnosis in high-prevalence areas significantly reduce the incidence of severe thalassemia. This review aims to summarize the genetic diagnostic approaches for thalassemia. Conventional genetic testing methods can identify 95–98% of thalassemia carriers but may miss rare thalassemia genotypes. Third-Generation Sequencing offers significant advantages in complementing other genetic diagnostic approaches, providing a basis for genetic counseling and prenatal diagnosis.